Emi filter techniques in power electronic converters (2010)
This paper presents the results of EMI reduction techniques applied to power electronic converters. The techniques applied included shielding control and power signals, separating power system references regarding reference for instrumentation and measurement signals, implementing analog filters and configuring an appropriate switch trigger system for electronic power to decrease shifting EMI emissions to the maximum. This paper presents the results before and after applying the techniques to reduce interference. The results were also veryfied by using two real time control strategies rapid control prototyping (RCP).